Pelatihan BTCLS (Basic Trauma Cardiac Life Support) Berbasis Blanded Learning untuk Meningkatkan Kompetensi Perawat dalam Kegawatdaruratan di Kota Mamuju - Yasirul Muntaha; Ashriady Ashriady; Marlina Fitriya Lailatul K; Edi Purnomo; Zulhaini Sartika; I Made Sudarta; Abbas Mahmud; Hermawati Hermawati; Andi Nasir (STIKES Marendeng Majene, 2026)
Emergency care services require nurses who are competent in initial assessment, resuscitation, and the management of trauma and cardiac arrest cases. However, not all nurses receive regular Basic Trauma Cardiac Life Support (BTCLS) training, highlighting the need for continuous competency development. This community service program aimed to enhance nurses' knowledge, skills, and preparedness through a blended learning–based BTCLS training program in Mamuju City. The training was conducted through online learning using a Learning Management System (LMS), combined with face-to-face sessions consisting of lectures, discussions, demonstrations, simulations, and case scenario–based practical exercises. Program evaluation was carried out using pre-tests, post-tests, skills assessments, and participant satisfaction surveys. This program is expected to improve nurses' competencies in emergency care management in accordance with BTCLS standards, expand access to flexible and sustainable training, and contribute to improving the quality of emergency care services and patient safety in Mamuju City.